Study of role of blood transfusion in obstetric emergencies - Patel, Vibhuti Pravinbhai; Patel, Rina V.; Shah, Parul T.; Patel, Chirag K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Blood Transfusion is recognized as one of the eight essential component of comprehensive emergency obstetric care which has been shown to reduce the maternal mortality.1,2 In developing country like India, efforts should be done to make blood and transfusion services well maintained and quickly available to reduce maternal morbidity from haemorrhage and thus decrease the incidence of maternal mortality. Aims & objectives: (1) To study clinical status of the patients at time of admission. (2) To study the role of antenatal visits in all patients required blood transfusion. (3) To study the effect of blood components on the patients’ health. (4) To screen out the patients of high risk pregnancy and treat them safely. (5) To study causes of maternal mortality. Methods: Retrospective study of requirement of blood transfusion in antenatal and postnatal patients who came in labour room during last 3 month period at tertiary care Centre, Ahmedabad. Results: during the whole study out of 2200 patients 440 patients required blood transfusion among which 70% required due to obstetric hemorrhage and 30% due to severe anemia (less than 7 gm/dl). Major associated complications in the transfused patients were anemia (34%) and PPH (36%). 4 patients expired among them 2 were due to development of DIC and septicemia, 1 due to severe anemia and 1 due to severe PPH. Conclusions: Ensuring a safe supply of blood and blood products and the appropriate and rational clinical use of blood. Strategies made to maximize the haemoglobin (Hb) level at the time of delivery as well as to minimize blood loss. Active management of the third stage of labour is required to prevent avoidable morbidities, such as PPH, Retained product of conception, and vaginal lacerations.